Myocysticercosis: A rare entity in pregnancy (Indian Journal of Case Reports, 2025)
The larval form of Taenia solium causes cysticercosis which involves the central nervous system, eyes, gastrointestinal system, skeletal muscles, and subcutaneous tissues. Isolated muscular involvement is rare with only a handful of cases reported in the literature. We present this case of a 24-year-old primigravida who was admitted at 35 weeks 2 days of gestation with severe preeclampsia with intrahepatic cholestasis of pregnancy with cholelithiasis with bilateral pedal edema and was diagnosed in the post-operative period to have myocysticercosis which poses a diagnostic dilemma. This should be considered in differential diagnosis in developing nations, and especially in endemic regions. High-resolution ultrasound was important in the diagnosis but magnetic resonance imaging was confirmatory. The treatment of choice is anti-helminthic drugs and oral steroid medications.